Analisis Perlakuan Akuntansi Aset Tetap Pada Rumah Sakit Umum Daerah Genteng - Shella Iko Sita; Andriana Andriana; Ririn Irmadariyani (UPT Penerbitan Universitas Jember, 2017)
Purpose of this research for to To know about suitability of management fixed assets at RSUD Genteng with GovernmentAccounting Standard 07 about accounting of fixed assets and Government Accounting Standard 08 about construction inprocess. This research is located in the RSUD Genteng. Collect the data through interview with respondent is chief ofaccounting division RSUD Genteng. Data analysis was performed with a model Miles and Huberman. The result of thisresearch indicate that there is mistake of depreciation expense in the presentation, It is not disclosure yet about base marking offixed assets, it does not deside yet capitalization policy of maintenance expense, There is fixed assets which the book value lessthen minimum value of capitalization in the list of fixed assets. Classification, measurement, depreciation, and disposal of fixedassets has appropriate with government accounting standart 07 and 08.